"تحليل العلاقة السببية بين الإنفاق العام والتضخم في الاقتصاد الجزائري (1990-2020) " - أميرة, دبار; بثينة, صحراوي; سارة, طواهرية (University of eloued جامعة الوادي, 2022)
"يعتبر الإنفاق العام من اهم الوسائل التي تتيح للدولة والحكومات التحكم في الاقتصاد الوطني، وذلك عن طريق زيادته او تخفيضه تبعا للحاجة ووفقا لقدرتها على ضمان التمويل وهذا ما يؤثر على المتغيرات الاقتصادية من بينها التضخم، الذي يعد هذا الاخير من أخطر المشاكل الاقتصادية التي تمس مختلف اقتصاديات دول العالم سواء كانت نامية أو متقدمة على حد سواء لما يحدث اختلالات تنعكس سلبيا على مختلف الموازين الاقتصادية الكلية. وهدفت هذه الدراسة إلى تحليل العلاقة السببية بين الإنفاق الحكومي والتضخم في الجزائر خلال فترة (1990-2020). حيث لاحظنا من خلال الدراسة ان معدل التضخم في الجزائر غير مستقر من سنة الى اخرى وكما لخصت الى علاقة في الأجل القصير وعلاقة توازنيه في الأجل الطويل بين الإنفاق العام والتضخم، كما لسياسة الإنفاق العام تأثير ضعيف وعكسي على معدل التضخم، أي كلما زاد الإنفاق العام انخفضت نسبة التضخم قليلا، ولكنها ظرفية مؤقته، وهو ما يوجب على الحكومة الجزائرية ضرورة ترشيد النفقات وبناء قاعدة اقتصادية من خلال التنويع الاقتصادي للانتقال من الإنفاق الريعي إلى الإنفاق المستدام. ""Public spending is one of The most important means of allowing The state and government to control the national economy by increasing or decreasing it according to need and according to its ability to guarantee funding This affects The economic variables including inflation, which is The most serious economic problems affecting various economies The countries of The world, whether developed or advanced alike, to the imbalances that adversely affect the various macroeconomic balances. This study aims to shade the relative relationship from government agreement and design in Algeria during the period (1990-2020). Where we have noticed through the study that the inflation rate in Algeria is unstable from one basket to another and as summarized in a short-term and long –term equilibrium relationship between public spending and inflation, as the public spending policy has a weak and adverse effect on the rate of inflation, that is the higher the public spending, the lower The inflation rate is little, but it is circumstantial and temporary, which requires the Algerian government to rationalize expenditures and build an economic base through economic to move from quarterly spending to sustainable spending. "
ماستر اقتصاد
Keywords: إنفاق عام، تضخم، علاقة سببية.; public expenditure،inflation،causation